Thicker than blood how racial statistics lie - Zuberi, Tukufu (University of Minnesota Press, 2001)
"In this volume, Tukufu Zuberi offers a concise account of the historical connections between the development of the idea of race and the birth of social statistics. Zuberi describes the ways race-differentiated data is misinterpreted in the social sciences and asks questions about the ways racial statistics are used, such as: What is the value of knowing the income disparities or differences in crime and incarceration rates between different racial groups? When these data are available, what should the principles be guiding their dissemination, interpretation, and analysis?"--Jacket.